Exploring the Allosteric Mechanism of Src Homology-2 Domain-Containing Protein Tyrosine Phosphatase 2 (SHP2) by Molecular Dynamics Simulations - Wang, Quan; Zhao, Wen-Cheng; Fu, Xue-Qi; Zheng, Qing-Chuan (Frontiers in Chemistry, 2020)
The Src homology-2 (SH2) domain-containing protein tyrosine phosphatase 2 (SHP2, encode by PTPN11) is a critical allosteric enzyme for many signaling pathways. Programmed cell death 1 (PD-1) could be phosphorylated at its immunoreceptor tyrosine-based inhibitory motif (ITIM) and immunoreceptor tyrosine-based switch motif (ITSM) and bind to SHP2 to initiate T cell inactivation. Although the interaction of SHP2-PD-1 plays an important role in immune process, the complex structure and the allosteric regulation mechanism remain unknow. In this study, molecular dynamics (MD) simulations were performed to study the binding details of SHP2 and PD-1, and explore the allosteric regulation mechanism of SHP2. The results show that ITIM has a preference to bind the N-SH2 domain and ITSM has almost the same binding affinity to N-SH2 and C-SH2 domain. Only when ITIM binds to N-SH2 domain and ITSM binds to C-SH2 domain can obtain the full activation of SHP2. The binding of ITIM and ITSM could change the motion mode of SHP2 and switch it to the activate state.